Konstruksi Keakraban Orang Mataraman: Kajian Sosiopragmatik Pisuhan Pada Film Pendek Woko Channel - Angelica, Wina Vinola; Purnomo, Sucipto Hadi (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Pisuhan (swearing) has long been considered by most Javanese people to be a rude expression that is taboo or not good to say. However, in reality, pisuhan is still used in everyday conversations, such as pisuhan in the Woko Channel short film, pisuhan is definitely functional as a messenger. mpatan is not only used to express negative emotions in the form of harsh, dirty words or cruel expressions. Swearing is also used to express positive emotions as a form of greeting, praise, or used to familiarize each other when interacting. This research aims to reveal the constructions built by village communities through pisuhan. This study is a qualitative descriptive study. The data collection method used is observation combined with recording techniques. Data analytics techniques use pragmatic social data analysis techniques. The results of this study are 1) meaning and function of pisuhan; 2) the relationship between pishuhan and Javanese characteristics; 3) pishuhan has an impact on social relations in society.